2020
DOI: 10.1038/s41598-020-73022-2
|View full text |Cite
|
Sign up to set email alerts
|

Late attentional processes potentially compensate for early perceptual multisensory integration deficits in children with autism: evidence from evoked potentials

Abstract: Sensory processing deficits and altered long-range connectivity putatively underlie Multisensory Integration (MSI) deficits in Autism Spectrum Disorder (ASD). The present study set out to investigate non-social MSI stimuli and their electrophysiological correlates in young neurotypical adolescents and adolescents with ASD. We report robust MSI effects at behavioural and electrophysiological levels. Both groups demonstrated normal behavioural MSI. However, at the neurophysiological level, the ASD group showed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 72 publications
2
16
0
1
Order By: Relevance
“…This is in line with results in the literature proposing alterations of MSI in ASD when using social information (for a review, see Feldman et al, 2018). Moreover, studies using a multisensory detection task of simple non-social information are clinical comparative studies (ASD vs Control subjects) and have demonstrated either equal multisensory facilitation to controls (Brandwein et al, 2015;de Boer-Schellekens et al, 2013;Stefanou et al, 2020;Stewart et al, 2016) or degraded multisensory facilitation in subjects with ASD (Ainsworth et al, 2021;Brandwein et al, 2013;Collignon et al, 2013;Molholm et al, 2020;Ostrolenk et al, 2019). Thus, our study is the first to investigate the mechanism of multisensory facilitation according to autistic traits and propose it as being improved in subjects with high-autistic traits.…”
Section: The Sensory Modality Effectssupporting
confidence: 87%
See 2 more Smart Citations
“…This is in line with results in the literature proposing alterations of MSI in ASD when using social information (for a review, see Feldman et al, 2018). Moreover, studies using a multisensory detection task of simple non-social information are clinical comparative studies (ASD vs Control subjects) and have demonstrated either equal multisensory facilitation to controls (Brandwein et al, 2015;de Boer-Schellekens et al, 2013;Stefanou et al, 2020;Stewart et al, 2016) or degraded multisensory facilitation in subjects with ASD (Ainsworth et al, 2021;Brandwein et al, 2013;Collignon et al, 2013;Molholm et al, 2020;Ostrolenk et al, 2019). Thus, our study is the first to investigate the mechanism of multisensory facilitation according to autistic traits and propose it as being improved in subjects with high-autistic traits.…”
Section: The Sensory Modality Effectssupporting
confidence: 87%
“…Thus, our study is the first to investigate the mechanism of multisensory facilitation according to autistic traits and propose it as being improved in subjects with high-autistic traits. This heterogeneity at the behavioral level could be the consequence of a distinct cortical network of MSI, as all studies using neuroimaging techniques demonstrated that sensory merging in ASD occurred at different topographies and latencies compared to control participants (Brandwein et al, 2013(Brandwein et al, , 2015Molholm et al, 2020;Russo et al, 2010;Stefanou et al, 2020). In addition, structural, anatomic, and functional differences in the superior temporal sulcus, an important site of audiovisual multisensory integration (for a review, see Beauchamp, 2010), have been demonstrated in participants with ASD compared to control participants (for a review, see Zilbovicius et al, 2013).…”
Section: The Sensory Modality Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding audiovisual (n = 4; 18%) and auditory-somatosensory integration (n = 1; <5%), the studies evaluated the speed of the SIP in response to simultaneous audition and visual stimuli in children with ASC compared to a control group (Brandwein et al, 2013(Brandwein et al, , 2015Molholm et al, 2020;Russo et al, 2010;Stefanou et al, 2020).…”
Section: [Insert Here Table 1]mentioning
confidence: 99%
“…Early stimulus processing can be measured electrophysiologically, for example, by means of event-related potentials (ERPs; Barry et al, 2009 ). For instance, the P200 component that is the peak positivity that occurs between 175 and 250 ms after a stimulus onset, is associated with early sensory processing steps including like stimulus registration, encoding, evaluation, and discrimination, early attentive mechanisms and selective attention, as well as the inhibition of further processing of competing information ( Näätänen, 1992 ; Korostenskaja et al, 2008 ; Barry et al, 2009 ; Lazzaro et al, 2009 ; Sur and Sinha, 2009 ; Stefanou et al, 2020 ). This component has been reported to be deficient in patients with ADHD, showing an upregulation ( Barry et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%